2018
DOI: 10.1007/s10120-018-0791-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of polyglycolic acid sheets and fibrin glue for prevention of bleeding after gastric endoscopic submucosal dissection in patients under continued antithrombotic agents

Abstract: The covering method using PGA sheets and fibrin glue has the potential to reduce post-ESD bleeding in patients receiving continued antithrombotic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 35 publications
1
47
1
Order By: Relevance
“…Two prospective nonrandomized studies that enrolled patients taking antithrombotic agents showed that the delayed bleeding rate was significantly lower in the tissue-shielding group than in the control group (6.7% vs 22.0%, P = 0.04; and 5.8% vs 20.8%, P = 0.041, respectively). 89,90 Kikuchi et al 91 also showed favorable results of the PGA sheet shielding method in a single arm study. Difficulty of PGA sheet delivery to the post-ESD wound through the working channel was technical; however, in a prospective study, Mori et al 92 developed a delivery station system and showed feasibility of the delivery device.…”
Section: New Endoscopic Approaches For Prevention Of Delayed Bleedingmentioning
confidence: 93%
See 1 more Smart Citation
“…Two prospective nonrandomized studies that enrolled patients taking antithrombotic agents showed that the delayed bleeding rate was significantly lower in the tissue-shielding group than in the control group (6.7% vs 22.0%, P = 0.04; and 5.8% vs 20.8%, P = 0.041, respectively). 89,90 Kikuchi et al 91 also showed favorable results of the PGA sheet shielding method in a single arm study. Difficulty of PGA sheet delivery to the post-ESD wound through the working channel was technical; however, in a prospective study, Mori et al 92 developed a delivery station system and showed feasibility of the delivery device.…”
Section: New Endoscopic Approaches For Prevention Of Delayed Bleedingmentioning
confidence: 93%
“…Tissue‐shielding method using PGA sheet and fibrin glue was one of the most common approaches for prevention of delayed bleeding after gastric ESD. Two prospective non‐randomized studies that enrolled patients taking antithrombotic agents showed that the delayed bleeding rate was significantly lower in the tissue‐shielding group than in the control group (6.7% vs 22.0%, P = 0.04; and 5.8% vs 20.8%, P = 0.041, respectively) . Kikuchi et al .…”
Section: Adverse Events Related To Gastric Esdmentioning
confidence: 98%
“…Artificial ulcers after ESD can be shielded using polyglycolic acid tablets and fibrin glue, which is expected to reduce the risk of postoperative hemorrhage . Kawata et al reported that polyglycolic acid tablets and fibrin glue could decrease the rate of postoperative hemorrhage. In addition, a study of medical adhesives found that patients given a medical adhesive had a lower rate of post‐ESD hemorrhage than the control group (0% vs 4.88%).…”
Section: Precautions Against Bleeding After Gastric Esdmentioning
confidence: 99%
“…Closure of endoscopic resection induced ulcers of the stomach with endoscopic clips has been performed for many years, 23 but recently, methods of covering the ulcers using polyglycolic acids sheets (PGA sheets) and fibrin glue have also been reported. 24,25 In addition, endoscopic handsuturing for defect closure using special forceps for grasping a needle with thread has also been developed, 26 and it is expected to be used in clinical practice in the near future. In the Core Sessions, three research presentations on the prevention of delayed bleeding were reported (94th, two; 96th, one).…”
Section: Current Status Of Therapeutic Endoscopy For Gastric Lesionsmentioning
confidence: 99%